2002
DOI: 10.1159/000064447
|View full text |Cite
|
Sign up to set email alerts
|

The Cytocaud: A Hair Cell Pathology in the Waltzing Guinea Pig

Abstract: The waltzing guinea pig displays severe inner ear dysfunction that involves both an auditory and a vestibular manifestation. The aim of this study was to characterize a pathological tail-like extension of the vestibular hair cells, the cytocaud. Our data suggest that nearly all type I hair cells in the waltzing guinea pig have cytocauds, which appear as membrane-bound tails containing mitochondria and cytoplasm that proceed in a basal direction toward the basement membrane. The extensions either attach to the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
14
0

Year Published

2004
2004
2016
2016

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 20 publications
(19 citation statements)
references
References 18 publications
5
14
0
Order By: Relevance
“…Similar actin-rich elements have also been observed in vestibular hair cells of the 'waltzing' guinea pig [Ernstson et al, 1969;Flock et al, 1979;Kanzaki et al, 2002]. Myosin decoration studies indicated that the actin filaments in cytocauds of shaker 2 mice and the waltzing guinea pig are oriented with their barbed (plus) ends directed to the base of the hair cell, consistent with growth in this direction [Flock et al, 1979;Sobin et al, 1982].…”
Section: Discussionsupporting
confidence: 59%
“…Similar actin-rich elements have also been observed in vestibular hair cells of the 'waltzing' guinea pig [Ernstson et al, 1969;Flock et al, 1979;Kanzaki et al, 2002]. Myosin decoration studies indicated that the actin filaments in cytocauds of shaker 2 mice and the waltzing guinea pig are oriented with their barbed (plus) ends directed to the base of the hair cell, consistent with growth in this direction [Flock et al, 1979;Sobin et al, 1982].…”
Section: Discussionsupporting
confidence: 59%
“…Although horizontal rotation-evoked nystagmus does not reflect the utricular function specifically, it is an effective way of identifying the affected animals (Canlon and Dulon, 1993;Kanzaki et al, 2002). Normal animals (controls) did not display any of these characteristics.…”
Section: Methodsmentioning
confidence: 99%
“…The filament rods were first described by Ernstson et al (1969) who named them ''rod-shaped inclusion bodies". They have since been called ''needles" by Flock et al (1979) and ''cytocauds'' by Kanzaki et al (2002). The rods consist of fimbrin and actin (Flock et al, 1979;Flock, 1981, 1983) and in some cases reach a length of 30 lm (Kanzaki et al, 2002).…”
Section: Introductionmentioning
confidence: 99%
“…2C,H, arrowheads). Some of the phalloidin-positive structures resemble actincontaining 'cytocauds', a malformation of stereocilia that has been described in animals with inner ear mutations affecting hair bundles (Kanzaki et al, 2002).…”
Section: Hc Proteins In Cells Differentiated From Inner Ear Progenitorsmentioning
confidence: 97%